The Use of Cooperative Learning to Enhance Students Engagement in English Classroom - Rafika Wulandari; Amirullah Abduh; Abdul Halim (International Journal of Language, Education, and Literature, 2025)
This study investigates the use of cooperative learning to enhance student engagement in the English classroom at SMP Negeri 1 Mare. Using a qualitative case study approach, data were gathered through observations and interviews involving one teacher and ten eighth-grade students. The research explores perceptions and challenges in implementing cooperative learning and seeks strategies for improvement. Findings indicate that both teacher and students perceive cooperative learning as highly beneficial. The teacher integrates strategies such as Think-Pair-Share, role assignments, and reflective questioning to foster active participation and collaborative learning. Students report increased motivation, reduced anxiety, and improved confidence in using English, especially in speaking and vocabulary tasks.However, challenges persist. Unequal participation, time management issues, and occasional group conflicts were observed. The teacher addresses these through structured group roles, frequent feedback, and adaptive support. Students also demonstrate problem-solving by improving communication and collaboration skills. The study concludes that cooperative learning promotes a more interactive, inclusive, and dynamic classroom environment. While implementation challenges remain, strategic adjustments and clear guidance can significantly enhance the effectiveness of cooperative learning. These insights offer practical implications for teachers seeking to optimize engagement in English language instruction through collaborative methods.